Reading series fiction : from Arthur Ransome to Gene Kemp - Watson, Victor (Routledge, 2000)
This book investigates the 'series' in children's literature. It explores the nature and appeal of series writing, it provides an historical overview and looks at the nature of literary criticism applied to children's literature.